Contextual Categorisation of Academics’ Conceptions of Teaching - Daniel, Scott; Mazzolini, Alex; Mann, Llewellyn (Scientia in educatione, 2017)
Background: Despite large-class research-based instructional strategies being ﬁrmly established in the literature, traditional teacher-centred lecturing remains the norm. This is particularly the case in physics, where Physics Education Research (PER) has blossomed as a discipline in its own right over the last few decades, but research-based strategies are not widely implemented. This variation in practice is underpinned by variations in beliefs and understandings about teaching. Studies investigating the spectrum of conceptions of teaching held by teachers and, in particular, academics have almost uniformly identiﬁed a single dimension from teacher-centred to student-centred. These studies have used a phenomenographic approach to capture the variety of conceptions of teaching, but have excluded contextual issues like class size. Research Question: How does class size aﬀect academics’ conceptions of teaching? Method: This study used an online survey to compare and contrast respondents’ experiences of small and large classes, and in particular lectures. The survey was promoted to Australian university academics from a range of disciplines, predominantly science, technology, engineering, and mathematics (STEM). Responses to the sets of small-class questions were analysed independently from the sets of equivalent large-class questions. For each respondent their small-class responses were categorised, where possible, as either being student-centred or teacher-centred, and likewise, independently, for their large-class responses. Results: In total, 107 survey responses were received. Of these, 51 had the sets of both their large- and small-class responses unambiguously categorised. Five of these were student-centred regardless of class size, and 17 of these were teacher-centred regardless of class size. All of the remaining 29 responses were teacher-centred in large classes, but student-centred in small classes. Conversely, none of the responses corresponded to a conception of teaching that was student-centred in large classes and teacher-centred in small classes. Implications: This result demonstrates that the one-dimensional analysis of conceptions of teaching along the spectrum of teacher-centred to student-centred is too simplistic. Conceptions are contextual. At the very least they depend on class size, and perhaps other factors. It conﬁrms the hierarchy of understanding from teacher-centred to student-centred reported elsewhere in the literature, with the added feature of an intermediate stage of diﬀering focus depending on class size. One recommendation from this ﬁnding is that teaching professional development programs should be focused on developing studentcentred conceptions and practices in large classes in particular, as this occurs infrequently but leads to the best student learning outcomes. Moreover, further research on contextspeciﬁc conceptions of teaching need to be explored.